KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK DI KECAMATAN CISARUA KABUPATEN BOGOR - Siti Rahayu Septiany; Beddy Iriawan Maksudi; Irma Purnamasari (Jurnal Governansi, 2016)
Various community responses tend to suggest that different types of public services suffered a setback which is mainly marked by numerous irregularities in the public service. Systems and procedures are complicated, and human resources were slow in providing the service, expensive, closed, and discriminatory and cultured not serve, but served also an aspect of public service spotlight, especially in terms of population administration one of them in the service of making electronic ID card.The research objective is to know the quality of the electronic ID card service in District Cisarua, Bogor regency.The theory that used to analyze the quality of service is a theory proposed by Parasuraman in Harbani Pasolong (2013) which has five dimensions of service quality to be able to successfully include the dimensions of tangible, reliability, responsiveness, assurance, empathy. The five dimensions above should be implemented fully for one another have relevance.This research used descriptive quantitative method by using questionnaires as the main instrument to data collect.These results indicate that the quality of the electronic ID card service in District Cisarua, Bogor regency according to respondents of employees included in the criteria for the interpretation of Good, while according to the respondents community service quality Electronic Identity Card in District Cisarua, Bogor regency included in the criteria Pretty Good. It is explained that the completion of this electronic ID card service can’t be resolved quickly due to the completion of this electronic ID cards involve other agencies, namely the Department of Population and Civil Registration in Bogor district is not authorized for card printing and database processing. Suggestions from this study recommend that the government give them the authority to process the district population database that can handle an error in the electronic ID card identity. Then the district should continue to strive to conduct socialization to the village office of each region, with emphasis to the village to mobilize RW and RT convey any information which would have informed to the public; Keywords: Service Quality of electronic ID cards